Morphological Features and Ki67 Immunohistochemical Analysis in Trophoblastic Diseases: A Five-Year Retrospective Study: Ki67 Immunohistochemical Analysis in Trophoblastic Diseases - Khan, Sana Ullah; Khattak, Noreen; Shareef, Hoor Gulalai; Tahir, Mohammad; Khan, Muhammad Salman; Nadeem, Saima (Pakistan Journal of Health Sciences, 2025)
Gestational trophoblastic disorders (GTDs) are characterized by aberrant trophoblastic growth, with entire moles, partial moles, and hydropic abortions looking identical, making diagnosis difficult. Ki67 immunohistochemistry quantifies cellular proliferation, improving diagnosis and disease progression prediction. Objectives: To investigate the morphological features of prenatal trophoblastic disorders and test the diagnostic accuracy of Ki67 immunohistochemistry in distinguishing between whole moles, partial moles, and hydropic abortions during a five-year period. Methods: A retrospective descriptive study examined 50 GTDs, including complete, partial, and hydropic abortions. Morphological examination was done on Hematoxylin and Eosin-stained sections, while Ki67 immunohistochemistry assessed proliferation. To assess Ki67 expression and clinical outcomes, descriptive statistics, ANOVA, and regression models were used. Results: Complete moles exhibited the highest Ki67 levels (mean: 3.8 ± 0.6), significantly differing from partial moles and hydropic abortions in terms of villous hydrops and trophoblastic proliferation (p<0.001). Ki-67 expression was strongly associated with the progression of chronic trophoblastic disease, with 60% of high Ki-67 cases advancing to persistent disease (p<0.05). Conclusions: Ki67 immunohistochemistry proves effective in diagnosing and prognosticating GTDs, particularly in distinguishing between subtypes. Incorporating Ki67 into routine diagnostic practices can improve accuracy and patient care, though further multicenter studies are needed to confirm these findings and address limitations, such as the small sample size.